The possibility of using (Model M-Score Beneish) to predict the earnings management by the lagging banks and placing them under trusteeship in the Iraqi environment. - Salman Al-azzawi, Nada; kadhim Al-anbagi, Ahmed Taher; Noaman Al-Shammari, Suaad Adnan (Opción, 2019)
This study aims to determine the extent to which Model M-Score Beneish can used to forecast troubled banks before default and place them under trusteeship. The research data indicated that all the banks that were placed under the tutelage of the Central Bank of Iraq were practicing the earnings management policy. Concluded this study that the banks that manipulate their profits are the banks it is more likely to be managed by a bad administration and may suffer in the near future from a delay in paying its financial obligations.